Penanggulangan Stunting Melalui Sosialisasi dan Edukasi Gizi Seimbang di Desa Tambang, Kabupaten Ponorogo, Jawa Timur - Tamara Adelia Nainggolan; Indri Pramudita; Adhinugraha Wirayudha Kusuma; Radja Alzeron Rizaldy; Christia Meidiana; Astrida Fitri Nuryani (Jurnal Pengabdian Kepada Masyarakat, 2023)
Stunting has become a serious health problem in Indonesia as it is associated with failure to thrive, brain development disorders, decreased mental abilities, poor health conditions, and low socio-economic capabilities. In 2020, the United Nations recorded that around 6.3 million Indonesian early childhood or toddler aged children experienced stunting, caused by nutritional deficiencies within the first two years of their lives, maternal malnutrition during pregnancy, and poor sanitation. Through the "Ibu Hebat Keluarga Sehat" (Great Mother, Healthy Family) program, which focuses on balanced nutrition education, it is hoped that the issue of stunting can be addressed by improving individuals' knowledge and skills. Posyandu cadres and PKK officials can implement the 10 common messages of balanced nutrition to combat stunting. Balanced nutrition, categorized by age, is also crucial for every family to know as it contributes to achieving a generation without stunting. This education includes 1. Providing knowledge on balanced nutritional health in addressing stunting and processing local food materials available in the Tambang Village into nutritious meals. 2. Conducting question-and-answer sessions with participants to assess their understanding of the provided material.